2017
DOI: 10.1111/jfpe.12537
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing nano TiO2 assisted decoloration process for industrial date syrup utilizing response surface methodology

Abstract: Titanium dioxide nanoparticle has been proposed to be capable of presenting new consequences in field of date syrup decoloration besides common industrial discoloring techniques like using carbon active. This nano structure was used as a photocatalyst in the presence of ultraviolet radiation to investigate the decrement in high color and turbidity of date syrup. Photocatalytic decoloration process was optimized using response surface methodology statistical design. The effect of TiO2 catalyst portion, date syr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…There is no difference in the moles numbers of reactants and products of WGS reaction (Equation ). Since; the equilibrium of WGS is not sensitive to the reaction pressure . Nevertheless, up to the equilibrium, pressure has a progressive effect on the WGS reaction .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no difference in the moles numbers of reactants and products of WGS reaction (Equation ). Since; the equilibrium of WGS is not sensitive to the reaction pressure . Nevertheless, up to the equilibrium, pressure has a progressive effect on the WGS reaction .…”
Section: Resultsmentioning
confidence: 99%
“…Since; the equilibrium of WGS is not sensitive to the reaction pressure . Nevertheless, up to the equilibrium, pressure has a progressive effect on the WGS reaction . Comparing Figure A‐C, show that GHSV have little impact on CO 2 formation.…”
Section: Resultsmentioning
confidence: 99%
“…ANOVA was accomplished to evaluate the statistical significance of three fitted models, which are seen in Table 4. The P ‐value lower than .05, higher F ‐value, the R 2 and the adjusted R 2 values closer to 1 describe the model significance 43,44,51,52 . Based on Table 4, P ‐value for methanol conversion, H 2 yield and CO yield responses were less than .0001, which present that the fitted models were highly statistical significant.…”
Section: Resultsmentioning
confidence: 86%
“…The P-value lower than .05, higher F-value, the R 2 and the adjusted R 2 values closer to 1 describe the model significance. 43,44,51,52 Based on Table 4, P-value for methanol conversion, H 2 yield and CO yield responses were less than .0001, which present that the fitted models were highly statistical significant. Moreover, the values of R 2 and Adj R 2 of responses were close to 1, which described models could illustrate the relation between independent parameters and responses (see Table 4).…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, pore volume and average pore size of Fe-Mn-Cu/ZrO 2 catalyst were lower compared to pure ZrO 2 , which would be because of the partial blockage of ZrO 2 pores during the sample synthesis. [66][67] F I G U R E 6 TGA curve for catalyst after the stability test methanol conversion was almost fixed during 40 hours initial on stream with 71.29%, and then started to decrease to 60.67% in the time period of 40 to 50 hours (see Figure 5A). Zhuang et al 68 observed that methanol conversion was approximately stable during 35 hours initial.…”
Section: Resultsmentioning
confidence: 98%